A field guide to the birds of Sri Lanka - Harrison, John; Worfolk, Tim (Oxford 2011. New York : Oxford University Press, 2011)
A fully comprehensive, modern field guide to all of the bird species in Sri Lanka. Featuring numerous colour illustrations and detailed descriptions of the key identification features, the book will be equally valuable for ornithologists and birdwatchers.
Keywords: BIRDS -- SRI LANKA-- IDENTIFICATION; BIRDS; Sri Lanka